Okoliczności fundacji klasztoru kanoników regularnych w Kraśniku - Bielak, Włodzimierz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The article presents the circumstances of founding the monastery of the Canons Regular of Lateran in Kraśnik. The author omitted the data contained in the foundation documents which had already been described in the literature on the subject. The paper focuses on the history of the Tęczyński family, whose founding activity was aimed at marking their position among the elite of medieval Poland - the times of the Tęczyński family's splendour, which followed the periods of crisis, were marked by successive foundations. In this context, the purpose of the monastery in Kraśnik was to emphasize the position of the new branch in the Topór coat of arms - Rabsztyńscy. Attention was also paid to the Tęczyński family’s connections with the Canons Regular formed at the Cracow Academy, where some members of this family studied. Finally, the author presented a mysterious and unexplained case of Jakub Oleśnicki, who, according to an old tradition, was regarded as a brother of the famous Cardinal Zbigniew – a member of the Corpus Christi Monastery in Cracow. If Jakub was indeed related to Cardinal Oleśnicki – though he was not his brother, but rather his nephew – the question of choosing the Canons Regular to run the monastery in Kraśnik would be obvious, as he would be a very close relative of the founder of the monastery, Jan Rabsztyński